The Effect of Acupressure Therapy in Obstructive Sleep Apnea - Galih Jatnika; Susilawati Hartanto (Universitas Kristen Maranatha, 2019)
Obstructive Sleep Apnea (OSA) is a respiratory disorder during sleep with characteristics of temporary breathing cessation and upper airway obstruction that recurred partially or completely. Obesity has been recorded as one important risk factor in OSA. The purpose of this research was to assess the effect of acupressure therapy in OSA. This is a quasi-experimental study with pre-test and post-test one group design. Respondents were 18 high school students with BMI > 25 kg/m2. OSA was assesed using Epworth Sleepiness Scale. Acupressure therapy was done at 10 acupoints for 10 consecutive days. Data was analyzed using dependent t test. The results showed Epworth Sleepiness Scale score decreased significantly after acupressure therapy procedure (6.78 vs 5.28; p value 0.004). Conclusion, acupressure therapy can reduce the severity of OSA. Keywords: acupressure, obesity, obstructive sleep apnea